Integrate (3x^2 - (1/4)x^-2 + 3) dx

3x2-(1/4)x-2+3
Split the problem into three separate terms and integrate independently.With any term where x is to the power of something, divide the coefficient by the value of the power plus 1.e.g. 3x2 ---> [3/(2+1)]x2 ---> x2But this is not your final answer. You must then take the power and plus 1.x2 ---> x2+1 ---> x3
Applying this to the question:3x2 ---> [3/(2+1)]x2+1---> x3(1/4)x-2 ---> [(1/4)/(-2+1)]x-2+1 ---> (-1/4)x-13 ---> 3x
Combined, this gives you:x3--(1/4)x-1+3x+C= x3+(1/4)x-1+3x+C

Answered by Lucy L. Maths tutor

3955 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The parametric equations of a curve are: x = cos2θ y = sinθcosθ. Find the cartesian form of the equation.


Can you explain the sum of 1 to 100?


A factory produces cartons each box has height h and base dimensions 2x, x and surface area A. Given that the capacity of a carton has to be 1030cm^3, (a) Using calculus find the value of x for which A is a minimum. (b) Calculate the minimum value of A.


Find dy/dx for y=5x^3-2x^2+7x-15


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences